The Role of Leadership Agility and Entrepreneurial Orientation on Innovation Ambidexterity and Its Impact on Competitive Advantage - Indriyani, Desty Sesiana; Utami, Hamidah Nayati; Afrianty, Tri Wulida (Jurnal Aplikasi Manajemen, 2024)
In a dynamic and competitive business landscape, understanding the pivotal factors influencing innovation performance is essential for small culinary businesses aiming to maintain a competitive edge. This study investigates how leadership agility and entrepreneurial orientation promote innovation ambidexterity and competitive advantage, focusing on their direct and indirect effects, particularly among small culinary enterprises. This explanatory research employs a quantitative approach. The population comprises all small culinary businesses in Madiun City, totaling 90 businesses. Using a census sampling technique, the entire population was surveyed. Data were collected through a closed questionnaire and analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. The results indicate that leadership agility and entrepreneurial orientation significantly enhance innovation ambidexterity. Likewise, leadership agility and entrepreneurial orientation significantly impact competitive advantage. Notably, innovation ambidexterity significantly mediates the relationship between antecedent factors and competitive advantage, underscoring its role as a crucial mechanism in this dynamic. The study's novelty lies in exploring these relationships within the under-researched context of small culinary businesses, offering fresh insights into how these enterprises can leverage internal capabilities for greater market competitiveness. These insights are valuable for business owners, policymakers, and stakeholders in designing strategies and policies to support the development and competitiveness of small businesses.